Case study: night compression use in a patient with Milroy's disease. (23rd June 2022) - Chohan, Ambreen; Sumner, Simon; Olivier, Mairi; Whitaker, Justine
Abstract : Aim: Lymphoedema is associated with dysfunctional lymphatics, tissue fibrosis and inflammatory changes in the skin and local tissue. Ensuring compression supports tissue health is crucial to managing lymphoedema. Providing patients with safe compression which enhances their tissue health is paramount when supporting their 24-hour self-management regimens. This case study explores the use of a new compression garment in two sitting positions in an adult with primary lymphoedema. Method: An 18-year-old female (body mass index 25.2 kg/m 2 ) with Milroy's disease was recruited. She attended two separate 1-hour sessions to evaluate tissue oxygenation (StO2 ) in chair-sitting and long-sitting (sitting up with a supported back and legs horizontal) positions. Following removal of her usual class 2 (20–30 mmHg) flat-knit compression hosiery, StO2 was recorded for 20 minutes: pre-, during and post the application of an adjustable compression garment (Lohmann & Rauscher) to the right leg. Results: In the long-sitting position, StO2 levels started high at baseline (94.5%), and were relatively maintained both during and post-a short 20-minute intervention (94.1%). In the chair-sitting position, StO2 levels were significantly lower at baseline (52%), showing a 77% increase during the intervention (92%), followed by a small 9% decrease post-intervention (83.7%). Conclusion: This compression garment significantly increased StO2 levels in the chair-sitting position, while maintaining the effects of the patient's compression stockings, in the long-sitting position. Similar to non-lymphoedematous limbs, the patient's normal prescription hosiery maintains StO2 . Through implementation of the short intervention sessions, night compression garments may have the potential to improve tissue health in individuals with primary lymphoedema, encouraging self-management and offering a potential night compression solution where the need arises in a 24-hour management plan.